2016
DOI: 10.1016/j.biopsych.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Memory and Its Enhancement by Estradiol Requires Surface Dynamics of Hippocampal CA1 N-Methyl-D-Aspartate Receptors

Abstract: NMDAR surface trafficking and its modulation by the sex hormone E2 is a cellular mechanism critical for a major component of episodic memory, opening a new and noncanonical research avenue in the physiopathology of cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…Interestingly, it has been reported that GluN2B-NMDAR surface dynamics are specifically altered when neurons are exposed to the extracellular protein reelin (Groc et al, 2007), to sexual hormone estrogen (Potier et al, 2016), or to strong synaptic activation (Dupuis et al, 2014). These paradigms have in common to be potent regulators of NMDAR-dependent synaptic maturation and plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that GluN2B-NMDAR surface dynamics are specifically altered when neurons are exposed to the extracellular protein reelin (Groc et al, 2007), to sexual hormone estrogen (Potier et al, 2016), or to strong synaptic activation (Dupuis et al, 2014). These paradigms have in common to be potent regulators of NMDAR-dependent synaptic maturation and plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…26,34 However, our current understanding of this process comes essentially from in vitro investigations based on primary cultures of neurons. Yet, key aspects of the regulation of NMDAR dynamics require intact brain preparations to be addressed, a challenge particularly obvious when considering the interplay between NMDAR and the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies by Srivastava et al (2006) were the first to demonstrate that treatment of cortical neurons with E2 resulted in transient removal of GluA1 from synapses; an effect that was accompanied by the synaptic insertion of the NMDA receptor subunit GluN1 suggesting formation of silent synapses. Conversely, increases in GluA1 surface expression have been observed in hippocampal neurons exposed to E2 (Zadran et al, 2009;Potier et al, 2015); an effect that has been attributed to the activation of ERβ as selective ERβ agonists mirror the E2-induced rise in surface GluA1 expression (Liu et al, 2008;Kramar et al, 2009). The subunit composition of hippocampal synaptic AMPA receptors also changes during the estrous cycle, indicating that fluctuations in endogenous estrogen levels also influence AMPA receptor trafficking in vivo (Tada et al, 2015).…”
Section: Regulation Of Glutamate Receptor Traffickingmentioning
confidence: 99%
“…Moreover, real time imaging studies have revealed rapid modulation of hippocampal NMDA receptor trafficking as acute exposure to E2 attenuates GluN2B surface expression, with no effect on surface GluN2A in hippocampal neurons (Potier et al, 2015). Although most studies have focussed on the role glutamate receptor trafficking in synaptic plasticity mechanisms during early postnatal development, activity-dependent alterations in the mobility of glutamate receptors also occurs in adult and aged hippocampus (Moga et al, 2006).…”
Section: Regulation Of Glutamate Receptor Traffickingmentioning
confidence: 99%